Rancang Bangun Sistem Kontrol Otomatis Berbasis Panel Surya pada Mesin Spinner Oil - Yanto, Putra Agung Dwi; Roza, Indra; Muthawali, Dede Ibrahim; Kusuma, Budhi Santri; Nasution, Agus Almi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Improving efficiency and sustainability in industrial processes is a key focus in modern technological development. This study aims to design an automatic control system for an oil spinner machine using renewable energy from solar panels. The system is intended to enhance operational efficiency, reduce reliance on conventional energy sources, and support environmentally friendly initiatives. It integrates sensors to monitor machine conditions such as speed and raw material levels, with a microcontroller unit connected to solar panels as an alternative energy source. The methodology includes system design, microcontroller programming, solar panel installation, and operational testing. Results show that the system successfully improved machine efficiency, reduced consumption of non-renewable energy, and contributed to lowering carbon emissions. This research provides a significant contribution to the development of renewable energy-based automation systems. It opens opportunities for similar applications in other industrial processes requiring efficient and eco-friendly solutions.